THE EFFECT OF MUDHARABAH FINANCING, MUSYARAKAH AND IJARAH FINANCING ON PROFITABILITY AT PT. BNI SYARIAH, Tbk. IN INDONESIA - Ade Fadillah FW Pospos (SEAN Institute, 2022)
This research was conducted to examine the effect of mudharabah, musyarakah and ijarah financing on profitability. The sampling technique used was purposive sampling with the criteria of Islamic Commercial Banks presenting and publishing quarterly financial reports for the period March 2015-December 2019, and the sample selected was BNI Syariah Indonesia. Data obtained from the official website of OJK and BNI Syariah. The method used is multiple regression analysis and hypothesis testing using t-statistics to test the coefficients together with the 5% level of significance. During the observation period, the results showed that the research data were normally distributed and no variables were found that deviated from the classical assumptions, which meant that the available data met the requirements to use the multiple regression equation model. The results of this study indicate that the Mudharabah Financing, Musyarakah and Ijarah Financing Variables jointly have a positive and significant effect on profitability at BNI Syariah in Indonesia (with a sig. value of 0.000 and a calculated F value of 22.911. Meanwhile, the Adjusted R Square value is 0.776 which means means that the independent variable in this model is able to explain 77.6% of profitability (ROA), while the remaining 22.4% is influenced by other factors not examined in this study.